2020
DOI: 10.3390/coatings10050469
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Particles with Langmuir Monolayers of 1,2-Dipalmitoyl-Sn-Glycero-3-Phosphocholine: A Matter of Chemistry?

Abstract: Lipid layers are considered among the first protective barriers of the human body against pollutants, e.g., skin, lung surfactant, or tear film. This makes it necessary to explore the physico-chemical bases underlying the interaction of pollutants and lipid layers. This work evaluates using a pool of surface-sensitive techniques, the impact of carbon black and fumed silica particles on the behavior of Langmuir monolayers of 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC). The results show that the incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…These results indicate that EG 12 NFs and EG 6 NFs were retained in the plane of the monolayer without desorption, even in the range of higher π ( Figure 9 , left). A similar π– A isotherm in the presence of hydrophobic nanoparticles had been reported [ 21 , 25 , 26 ]. Third, the ε 0 -π plot demonstrated that NFs caused a significant decrease in the maximum ε 0 value irrespective of EG length ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results indicate that EG 12 NFs and EG 6 NFs were retained in the plane of the monolayer without desorption, even in the range of higher π ( Figure 9 , left). A similar π– A isotherm in the presence of hydrophobic nanoparticles had been reported [ 21 , 25 , 26 ]. Third, the ε 0 -π plot demonstrated that NFs caused a significant decrease in the maximum ε 0 value irrespective of EG length ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 82%
“…Typically, an increase in π upon injection of some additives, such as polymers and nanomaterials, to the subphase can be attributed to lipid molecules condensation due to lipid–additive interactions. Two possible scenarios in which phospholipid packing can be more condensed due to the interaction with additives are described as follows: (i) the additives interact electrostatically with phospholipid molecules, leading to reduction in the repulsive forces between the lipid molecules [ 11 , 12 ]; (ii) the additives incorporate to the water–air interface via hydrophobic interactions with the hydrophobic tail of the phospholipids [ 13 , 25 , 41 ]. These interactions can lead to a decrease in the phospholipids’ available area and an increase in π.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to difficulties in studying the biological processes that take place on or within the natural membranes, resulting from the high complexity of such structures, research in this area is performed with the use of biomimetic model membranes [2]. It has been proven that their application allows the assessment of changes in the physicochemical properties of lipid layers caused by foreign substances [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most important advantage of this method is the possibility of investigating not only a cell’s overall response but also a mechanism of nano–bio interactions at the molecular level. The Langmuir monolayers were extensively used as cell membrane models in studies on the interactions between different kinds of nanoparticles and phospholipids [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%